Psychology and cognitive sciences: Past, present and future - Jacomuzzi, Alessandra Cecilia; Vecchi, Tommaso; Paterno, Sonia (Ricerche di Psicologia - Open Access, 2025)
Psychology and cognitive sciences and comprise a discipline whose history has been inherently intertwined and inseparable. While the scientific community distinguishes between these two disciplines, such clarity may not necessarily be apparent at the level of common understanding. In this article, we aim to delineate the historical relationship between these disciplines to elucidate both disparities and points of convergence. We will commence with an exploration of the historical trajectories of each discipline, culminating in an analysis of their intersecting junctures. We will elucidate the outcomes of their collaborative trajectories and examine the current perspectives that have emerged as a result. Finally, we will endeavor to discern whether the proximity between these disciplines may undergo transformation in light of the significant influences of neuroscience and artificial intelligence, and we will consider the prospects for their future collaboration.